2016
DOI: 10.18280/ijht.34sp0233
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pH effect on methane production from buffalo manure anaerobic Digestion

Abstract: Anaerobic digestion is an established technology to treat different kinds of wastes and to simultaneously produce biogas, a mixture of methane and carbon dioxide, which is a useful and renewable energy source. In this work, the anaerobic digestion of buffalo manure is studied. The latter is a low cost substrate rich in carbohydrates, especially suitable to produce biogas in anaerobic digesters. The process is performed both under mesophilic (37 °C) and thermophilic (55 °C) conditions with pH spanning from 6.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, the range of 5.5–6.5 is more favourable for the activity of hydrolytic and acidogenic bacteria. The pH of the bioreactor is a critical factor for the decomposition of the anaerobic digester as it may cause perturbations on the microbiome dynamics and the subsequent metabolomic pathways (Carotenuto et al, 2016). Microbial activity is inhibited when the microbiome is exposed to low pH values, which impedes the digester operation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the range of 5.5–6.5 is more favourable for the activity of hydrolytic and acidogenic bacteria. The pH of the bioreactor is a critical factor for the decomposition of the anaerobic digester as it may cause perturbations on the microbiome dynamics and the subsequent metabolomic pathways (Carotenuto et al, 2016). Microbial activity is inhibited when the microbiome is exposed to low pH values, which impedes the digester operation.…”
Section: Resultsmentioning
confidence: 99%
“…In the control system, the temperature range as set is [36°C -38°C]. The optimal temperature of anaerobic digestion in the mesophilic domain is around 37°C (Gavala et al, 2003;Carotenuto et al, 2016). Thus, as soon as heating starts, the temperature of the substrate at which it must be cut is 38°C, and…”
Section: Control Strategymentioning
confidence: 99%
“…Equation 3predicts a CH 4 /CO 2 ratio ranging from 1, for simple carbohydrates like starch (C 6 H 10 O 5 ) n , or proteins (C 5 H 7 NO 2 ) to 2.35, for the conversion of lipids, e.g., C 57 H 104 O 6 . It is experimentally found that for the fermentation of water buffalo manure the CH 4 /CO 2 ratio is about 2 [39,40]. Being 2 is an intermediate value among the possible ones, we keep the CH 4 /CO 2 ratio constant and equal to 2 in all the biogases investigated in our simulations.…”
Section: Fuelsmentioning
confidence: 99%